Anomalious Trends in Electromagnetic As Earthquake Precursors With Related Parameters at the Port Ratu Observatory - Angga Setiyo Prayogo; Bambang Sunardi (Natural B, Journal of Health and Environmental Sciences, 2015)
Research on electromagnetic anomalies as earthquake precursor was performed in many places and time. Pelabuhan Ratu Observatory. For validation, correlation between anomaly value and time length with earthquake that recorded at Pelabuhan Ratu Geophysical Observatory and have electromagnetic anomaly. Goals of this research were analyze correlation between anomaly pattern value and time length to earthquake magnitud and Rhypo. Data processed by polarization ratio and impedance of electromagnetic at ultra low frequency spectrum, the correlation method using regression and physical analysis between parameter. Data that used was electromagnetic and earthquake data that recorded and perceived at geophysical observatories of Pelabuhan Ratu. Results of electromagnetic anomaly value with magnetic polarization ratio was varies in 0.1 until 9.5, and also time length between 4 until 39 days before earthquake. Value of anomaly with impedance method was varies in 3.01 until 16.1, and also time length between 4 until 32 days before earthquake. In conclusion, known that trend correlation of the appearance of anomalous values and ranges of magnitude and distance Rhypo with magnetic polarization method showed a positive correlation, whereas a negative correlation with the impedance method. Negative correlation also obtained on relationship between Rhypoand magnitude of the span of time and the value of the polarization anomaly